CHEMICAL CONTROL OF ASCOCHYTA BLIGHT OF CHICKPEA - MANINDER SINGH, GURDIP SINGH AND (Indian Phytopathology, 2002)
Primary seed-borne infection of ascochyta blight [Ascochyta rabiei (Pass.) Lab.) of chickpea (Cicer arietinum L.) can very effectively be controlled by treating the seed with fungicides. Combinations of bavistin + thiram (1 : 1, 1 : 3) 3 glkg of seed gave 95-100 per cent disease control. Bravo (6 ml), hexacap (4 g) and thiabendazole (5 g/kg of seed) completely eliminated the seed-borne infection. Rovral and hexacap (3 g/ kg of seed) gave 98 per cent disease control. Foliar sprays of bravo (1500 ml) and calixin-M (900 g/ha) were significantly superior to other fungicides in controlling the secondary infection followed by rovral (750 g) and hexacap (900 g/ha) in 300 litres of water.